Efficacy and safety of Jinlida granules as an adjuvant treatment for diabetic nephropathy: a systematic review and meta-analysis - Dai, Bo; Chen, Yanxu; Xiao, Yang; Chen, Jinying; Zhu, Zexin; Zhang, Peng; Zhang, Jieyu; Sun, Jian; Bao, Pengjie; Nan, Zheng; Zhang, Qi (Frontiers in Endocrinology, 2026)
ObjectiveJinlida Granules (JLD), a patented traditional Chinese medicine, has demonstrated significant efficacy when used as an adjunct treatment for DN. This meta-analysis systematically evaluated the efficacy, safety, and renoprotective effects of JLD as adjunctive treatment in DN patients.MethodsWe systematically searched the Chinese literature databases (China National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal Database) and English literature databases (PubMed, Web of Science, Cochrane Library, and Embase) from inception to September 2025 and included relevant studies published in Chinese and English after screening according to predefined inclusion and exclusion criteria. Meta-analysis and bias assessment of the included studies were conducted using Stata 16 and Review Manager 5.4.1 software. The quality of included studies was evaluated using the risk-of-bias tools outlined in the Cochrane Handbook.ResultsThis study analyzed data from 13 randomized controlled trials (RCTs) with 1,333 participants, including 658 participants in the control group and 675 participants in the treatment group. As an adjunctive therapy for DN, JLD treatment enhances clinical efficacy rate [RR = 1.30 (95% CI: 1.21, 1.39), I² =27%] and reduces the levels of serum creatinine (SCr) [SMD = -2.01 (95% CI: -2.33, -1.69), I² =80.0%], blood urea nitrogen (BUN) [SMD = -0.79 (95% CI: -1.07, -0.52), I² = 80%], 24-h urine protein test (24h-UTP) [SMD = -1.44 (95% CI: -1.88, -1.00), I² =89%], urinary albumin excretion rates (UAER) [SMD = -2.14 (95% CI: -2.97, -1.30), I² =92%], fasting plasma glucose (FPG) [SMD = -0.63 (95% CI: -1.01, -0.24), I² =83%], 2-h plasma glucose (2hPG) [SMD = -0.71 (95% CI: -1.20, 0.23), I² =89%], hemoglobin A1c (HbA1c) [SMD = -0.95 (95% CI: -1.55, -0.35), I² =92%], total cholesterol (TC) [SMD = -0.91 (95% CI: -1.75, -0.08), I² =92%], triglycerides (TG) [SMD = -3.07 (95% CI: -6.06, -0.08), I² =99%], vascular endothelial growth factor (VEGF) [SMD = -1.50 (95% CI: -2.53, -0.48), I² =95%], IGF-1 [SMD = -0.59 (95% CI: -0.97, -0.21), I² =74%], IL-6 [SMD = -1.77 (95% CI: -2.46, -1.09), I² =81%], TNF-α [SMD = -1.75 (95% CI: -2.37, -1.13), I² =88%], and high sensitivity C-reactive protein (hs-CRP) [SMD = -2.48 (95% CI: -2.81, -2.15), I² =54%]. For adverse reactions, the pooled risk ratio was 0.71 (95% CI: 0.42, 1.20, I² = 0%) in the JLD adjunct therapy group relative to controls. The 95% CI crossing 1 indicated no statistically significant difference in adverse reaction rates, and no reliable conclusion regarding the safety superiority of JLD could be drawn.ConclusionsJLD as an adjunctive therapy enhances renal function, glucose and lipid metabolism, inflammatory regulation, and vascular health in patients with DN. Meta-analysis revealed no statistically significant differences in safety outcomes, indicating that safety remains a matter of debate.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251148725, identifier CRD420251148725